Bidirectional Chemo-Mechanical Interface Stabilization in Perovskite Solar Cells - Qian Cheng; Xiaofen Li; Mingwei Hao; Kuan Wang; Jiahong Tang; Pengfei Guo; Lifei He; Wenjian Yu; Changyu Yang; Du Chen; Peijun Guo; Yuanyuan Zhou (Journal of the American Chemical Society, 2026)
Abstract The interface structures between dissimilar layers in perovskite solar cells (PSCs) are prone to the concurrent occurrence of lateral (in-plane) chemical aggregation and vertical (out-of-plane) mechanical delamination. This issue severely affects long-term optoelectronic processes in PSCs, and it has not been addressed holistically. Herein, we introduce an ultrathin interfacial layer of 1,3,6,8-pyrenetetrasulfonic tetrasodium salt (PTS) to stabilize the perovskite/C60 interface at the molecular level. The sulfonate groups in PTS molecules anchor to the perovskite interface, while the parallelly aligned pyrene cores establish robust π–π interactions with C60 molecules. The reconstructed interface enhances the interfacial adhesion and restricts the mobility of C60 molecules, enabling a bidirectional chemo-mechanical interface stabilization (BCIS) mechanism at the perovskite/C60 interface. The resultant PSCs deliver power conversion efficiencies (PCEs) of up to 26.53%, showing 96% PCE retention after 1,000 h maximum-power-point tracking (ISOS-L-1l), and 91% PCE retention after 300 thermal cycles (−40 to 85 °C, IEC61215 MQT11). The scalability of PTS treatment is demonstrated by the 818 cm2 (aperture area) perovskite solar modules (PSMs) with PCEs over 20% using industrial-compatible manufacturing processes under 55% relative humidity (RH). This work underscores bidirectional interface engineering as a critical strategy for advancing commercially viable perovskite photovoltaics.